Exploring The Figurative Language Landscape In “Moana” Movie (A Semantics Analysis on Figurative Language) - Tinambunan, Toibah Hasanah; Sihite, Meida Rabia; Prihatini, Syafrina (EXCELLENCE: Journal of English and English Education, 2024)
The goals of the research were to identify the many forms of symbolic language employed in the film "Moana" and to provide an analysis of the symbolic language's contextual significance. A descriptive qualitative approach was used to carry out the research in this study. The actors' and actresses' dialogues from the film Moana were analyzed using the text transcribed version of the film. Metaphor(25.66%), metonymy(12.38%), hyperbole(17.69%), personification(9.37%), simile(0.88%), irony(22.12%), symbolism(7.96%), and paradox (3.53%) were the eight forms of figurative language identified in the Moana animated film. In addition, the researchers found that the meaning of each figure of speech varied depending on the situation in which it was used.